“Savages at the End of the World”: Robert Lehmann-Nitsche and his Studies of the Indigenous Peoples of Patagonia, 1898-1919 - Ballestero, Diego (Revista de Antropologia, 2019)
One of the first research interests of the German anthropologist and ethnologist Robert Lehmann-Nitsche (1872-1938), upon assuming the position as head of the Department of Anthropology at the La Plata Museum in Argentina (Sección de Antropologia del Museo de La Plata), concerned the indigenous peoples of Patagonia. This article explores Lehmann-Nitsche’s anthropological, ethnological, and linguistic studies among the indigenous peoples of Patagonia (Selk'nam, Gennakenk, Mapuche, Aónikenk, Kawésqar, and Yaghan) conducted between 1898 and 1919. These studies included research into pathology, craniology, anthropometry, archaeology, ethnology, linguistics, and mythology. He aimed at contributing to contemporary theories of German scholars on the development and characterization of “natural peoples” (Naturvölker), as opposed to “cultural peoples” (Kulturvölker), asserting a basic division of humanity.